Future approaches to clearing the latent human immunodeficiency virus reservoir: Beyond latency reversal - Alexander M.L. Hayes (AOSIS, 2020)
Background: While combined antiretroviral therapy (cART) allows near-normal life expectancy for people living with human immunodeficiency virus (HIV), it is unable to cure the infection and so life long treatment is required. Objectives: The main barrier to curing HIV is the latent reservoir of cells, which is stable and resistant to cART. Method: Current approaches under investigation for clearing this reservoir propose a 'Shock and Kill' mechanism, in which active replication is induced in latent cells by latency reversal agents, theoretically allowing killing of the newly active cells. Results: However, previous studies have failed to achieve depletion of the T central memory cell reservoir, are unable to target other latent reservoirs and may be causing neurological damage to participants. Conclusion: Future approaches to clearing the latent reservoir may bypass latency reversal through the use of drugs that selectively induce apoptosis in infected cells. Several classes of these pro-apoptotic drugs have shown promise in in vitro and ex vivo studies, and may represent the basis of a future functional cure for HIV.